Phosphorus levels for goats: endogenous fecal loss and net requirement for maintenance - Bueno, Mauro Sartori; Vitti, Dorinha Miriam Silber Schmid (Pesquisa Agropecuaria Brasileira, 1999)
Nine male castrated Alpine goats were used and the experiment was repeated twice. Animals were fed a diet consisted of hay and concentrate mixture without P supplementation, or with different amounts of dicalcium phosphate to give 1g or 2 g P/animal/day for 28 days. At the 21st day, 7,4 MBq 32P were injected through jugular vein into each animal; and feces, blood and urine samples were collected during seven days to determine the P metabolism. Total fecal P, absorbed P, endogenous fecal P, efficiency of absorption, feces and plasma P levels were positively related to P intake. The relationship between P intake (X) and endogenous fecal P (Y) is described by the equation: Y=10.36 + 0.58 X (r=0,94). The minimum endogenous P was 10,36 mg/kg live weight/day and efficiency of absorption was 65,76% for the supplemented treatments. Saliva P level was not related to P intake and there was not P excretion in the urine.